Rationale and Study Design of a Randomized Clinical Trial of Metformin to Prevent Frailty in Older Adults With Prediabetes. (19th March 2019) - Espinoza, Sara E; Musi, Nicolas; Wang, Chen-pin; Michalek, Joel; Orsak, Beverly; Romo, Terry; Powers, Becky; Conde, Alice; Moris, Melody; Bair-Kelps, Darcy; Li, Yan; Ganapathy, Vinutha; et al.
Abstract: Background: Frailty is a geriatric syndrome that leads to poor health outcomes with aging. Previous studies have demonstrated that insulin resistance and inflammation predict frailty onset. Metformin is a widely used, well-tolerated drug that improves insulin sensitivity and displays anti-inflammatory properties. It is also known to prevent diabetes onset in adults with prediabetes. We hypothesize that metformin in older adults with prediabetes will promote healthy aging and prevent frailty. Here we describe an ongoing placebo-controlled, double-blinded clinical trial of metformin for the prevention of frailty in older adults with prediabetes. Methods: Older adults aged more than 65 years are randomized to metformin or placebo and are followed for 2 years. Prediabetes, required for inclusion, is assessed by 2-hour oral glucose tolerance test. Exclusion criteria are baseline frailty (Fried criteria), diabetes, dementia, untreated depression, active malignancy, or severe cardiovascular, pulmonary, and neurologic diseases. Primary outcome is frailty; secondary outcomes are physical function (Short Physical Performance Battery), systemic and skeletal muscle tissue inflammation, muscle insulin signaling, insulin sensitivity (insulin clamp), glucose tolerance (oral glucose tolerance test), and body composition (dual-energy x-ray absorptiometry). Subjects are followed every 3 months for safety assessments and every 6 months for frailty assessment (Fried criteria) and oral glucose tolerance test, and every 12 or 24 months for secondary outcomes. Enrollment of 120 subjects (completers) will take place over a 2-year period. Conclusion: Metformin is being examined in this study as a potential therapeutic agent to prevent frailty in older adults with prediabetes. Findings from this trial may have future implications for the screening and potential treatment of prediabetes in older patients with metformin for the prevention of frailty.